Smart solution for reducing the COVID‐19 risk using smart city technology. Issue 2 (6th July 2020) - Jaiswal, Rahul; Agarwal, Anshul; Negi, Richa
Abstract : The COVID‐19 is not mitigating without a vaccine, but its effect can reduce using some advance technology. Smart cities are one of the essential needs for reducing this pandemic. This study presents the role and implementation of smart city technology to minimise the COVID‐19 risk. The smart city technology is used to maintain social distancing, which avoids the face‐to‐face interaction and physical contact. It has been observed that the position technology is used to trace the infected people. Drones and robot technology are used to work as medical staff and helpful for other essential services. It can be seen that smart healthcare is one of the advance smart city technologies, which is used to take care and treat infected people without any contact. It has also been observed that the smart delivery system is one of the contact‐free technologies. It is used to deliver essential items, including groceries, food, and medicine, without any physical contact. The uses of all the above smart city technologies have been discussed widely to mitigate the COVID‐19 risk.